ANALISIS KINERJA RUAS JALAN AKIBAT BEROPERASINYA SMP NEGERI 1 BLAHBATUH DAN TIDAK BEROPERASINYA SMP NEGERI 1 BLAHBATUH - I Dewa Ayu Dwi Darmayanti; Ni Made Widya Pratiwi; Putu Aryastana (Inersia: Jurnal Teknik Sipil, 2024)
Activities at school have a direct impact on traffic, especially during school hours. Side obstacles that worsen road performance and increase delays, along with vehicle entry and exit activities to or from school, disrupt traffic performance. While the presence of rise and pull is not a cause of decreased road performance, behavior that does not comply with traffic signs often is. This research uses data collection techniques by direct observation to gather the necessary data at the research site. This observation was carried out directly and lasted for one day to obtain road geometric data, traffic volume, side obstacle data, speed, and trip generation data. Changes were observed in vehicles leaving and heading to SMP Negeri 1 Blahbatuh during the survey time. The magnitude ranged from 0.8 second/hour to 173.8 second/hour. The low conditions occurred between 08.45-09.45 and the highest conditions between 06.30-07.30. The peak time for the departure or arrival of vehicles at SMP Negeri 1 Blahbatuh is 06.30-07.30. When SMP Negeri 1 Blahbatuh operates during peak hours, the traffic volume is less than when it is not operating. It is known that the saturation level fell by 27.39%, traffic volume fell by 1.19%, and road capacity remained unchanged. It is also known that at the peak of trip generation there was a decrease in traffic volume by 10.51%, an increase in road capacity by 4.45%, and a decrease in saturation levels by 29.33% when SMP Negeri 1 Blahbatuh was operating compared to when it was not operating.